Twitter sentiment classification using Naive Bayes based on trainer perception - Ibrahim M.N.M.; Yusoff M.Z.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
E-learning; Social networking (online); Supervised learning; Malaysia; Naive bayes; Sentiment classification; Three categories; Classifiers